Impact of Human Dermal Microvascular Endothelial Cells on Primary Dermal Fibroblasts in Response to Inflammatory Stress - Sanchez, Benjamin; Li, Linan; Dulong, Joshua; Aimond, Géraldine; Lamartine, Jérôme; Liu, Guangrong; Sigaudo-Roussel, Dominique (Frontiers in Cell and Developmental Biology, 2019)
The aim of the present study was to evaluate the impact of the microenvironment produced by dermal microvascular endothelial cells, secondary to a pro-inflammatory challenge, on 2D culture models using dermal fibroblasts and in 3D reconstructed skin model using dermal fibroblasts and keratinocytes from healthy donors. We hypothesized that specific microvascular endothelial low grade inflammation could change fibroblasts phenotype and be involved in extracellular matrix modification and skin alteration. Following IFN, TNF, IL-1 pro-inflammatory stress on Human Dermal Endothelial Cells (HDMEC) we observed the increased release of CCL2, IL-6 and IL-8 but not VEGF-A in the conditioned medium. The subsequent addition of this endothelial pro-inflammatory conditioned medium in dermal fibroblasts revealed an upregulation of IL6, IL8 and CCL2 but no NF-κ gene expression. The resulting extracellular matrix formation was impaired with a reduction of the collagen 1 network and a decrease in COL1A1 gene expression in 2D and 3D models. Collagen 1 and pro-LOX protein expression were significantly reduced confirming an impairment of the collagen network related to endothelial inflammation secretion. To conclude, this work showed that, without any immune cells, the endothelial secretion in response to a pro-inflammatory stress is able to activate the fibroblasts that will maintain the pro-inflammatory environment and exacerbate extracellular matrix degradation.